A preliminary study for the photolysis behavior of biodiesel and its blends with petroleum oil in simulated freshwater. (1st January 2015) - Yang, Zeyu; Hollebone, Bruce P.; Wang, Zhendi; Yang, Chun; Brown, Carl; Zhang, Gong; Landriault, Mike; Ruan, Xinchao
Highlights: For FAMEs, higher degree of saturation resulted in lower transformation. Water matrices, initial concentration of biodiesel affected degradation slightly. Biodiesel source effect can be neglected. Presence of biodiesel stabilized the small oil droplets in aqueous phase. Biodiesel inhibited the degradation of some heavy hydrocarbons. Abstract: With the increasing use of biodiesel and its blends with petroleum fuel, the corresponding environmental issues also occur during its production, application and transportation. The photolysis behavior for biodiesel and the impacts of biodiesel on the photo-oxidation of petroleum hydrocarbons in simulated freshwater was studied by irradiated with ultra violet (UV) and simulated sunlight in the present study. The results indicated that the photolysis rates of fatty acid methyl esters (FAMEs) were mainly depended on their degree of saturation, slightly on water matrices and the initial concentration of biodiesel, regardless of biodiesel sources. Similar results were observed for total organic carbon (TOC) removal rates; however, TOC removal rates were slightly dependent on the initial concentration of biodiesel. The presence of humic acid and pyrogallic acid or lake water matrices slightly inhibited the removal rates of TOC. The photolysis rates of individual petroleum hydrocarbons with and without the presence of biodiesel followed similar rules. In brief, alkanes with light molecular weights were transformed faster than those with heavy molecules, the removal of polycyclic aromatic hydrocarbons (PAHs) were more significantly than alkanes, and the removal of alkylated PAHs (APAHs) increased concurrently with the alkylation level in each family. The presence of biodiesel only inhibited the photolysis of some heavy alkanes and PAHs, not for all other petroleum hydrocarbons. Biodiesel, as a surfactant-like material, could stabilize small oil droplets initially formed by agitation, therefore, these droplets experience longer lifetimes in the water phase before re-aggregating into larger globules and rising to the surface. The apparent solubility of petroleum hydrocarbons, especially for those with heavier molecular weights, has been enhanced in the presence of FAMEs. In this scenario, light needs to penetrate water phase to degrade these targets compared with diesel alone. The direct contacting opportunities between UV light and targets, and radicals produced to attack targets were reduced, which finally resulted in the inhibited photolysis rates of some heavy molecular weight hydrocarbons.